THEORETICAL BASIS OF IMPLEMENTING PREVENTIVE POLICY IN LEGAL EDUCATION - Ibragimov Shukhrat Isroilovich (The Conference Hub, 2025)
The implementation of a preventive policy in legal education plays an important role in developing a legal culture in society and preventing crimes. This policy is aimed at providing citizens with legal knowledge and ensuring their understanding of their rights and obligations. The implementation of a preventive policy through legal education helps to increase social stability in society, resolve conflicts constructively, and reduce crimes. Therefore, the introduction of a preventive policy in legal education serves to make society more just and safe.
Keywords: Legal education, preventive measures, effective implementation, principles.